STEAM at the University for Older Adults. Challenges of education in active ageing - Ajuriaguerra Escudero, Miguel Angel (Journal of Learning Styles, 2025)
STEAM, a crucial skill in the contemporary world, is a fundamental element in education. However, it poses a unique challenge in higher education for individuals over 55. This article details the methodology employed over three academic years at the Senior University, a place with a strong educational and formative ethos that champions active ageing. The diverse student body, with varying backgrounds and interests, presents both a challenge and an opportunity in the classroom. Despite most students opting for humanities-related subjects, the program introduces a new STEAM methodology tailored for senior students, promoting the use and application of new technologies. This approach is significant as it enables students to apply their skills in other subjects and in their daily lives. The results obtained after the methodological application have been remarkably satisfactory among students and teachers. This not only satisfies the students’ need for knowledge but also develops new skills that promote active ageing, offering a promising outlook for the future.